Response of two mungbean varieties grwon on sandy soil to foliar application with some micronutrients - Abou Zied, S.T.; El-Naggar, A.M.A.; El-Kramany, M.F.; Essa, R.E.Y.; Nofal, O.M.A.; Khalifa, R.Kh.M. (2008)
Field experiments were carried out during the two consecutive summer seasons 2004and 2005 at E1-Fendan. Ismailia Governorate, Egypt to study the effect of foliar application of zinc. manganese and boron on yield, yield components and Chemical constituents of seeds of mungbean varieties
Includes reference.
Summary in Arabic.
1
Keywords: Mung bean -- Varietes; Mung bean -- Fertilizers; Sandy soils; Foliar feeding; Trace elements in plant nutrition